2017
DOI: 10.5152/tud.2017.45793
|View full text |Cite
|
Sign up to set email alerts
|

Is standard percutaneous nephrolithotomy still the standard treatment modality for renal stones less than three centimeters?

Abstract: Objective: The aim of study was to compare the efficiency and safety of standard percutaneous nephrolithotomy (sPNL) and miniaturized percutaneous nephrolithotomy (mPNL) in lower calyx and/or pelvic stones smaller than three centimeters. Material and methods:From October 2010 to August 2015, 108 mPNL and 176 sPNL procedures were performed for renal stones smaller than three cm and located in the lower calyx and/or renal pelvis. All patients were evaluated preoperatively with intravenous pyelography and/or comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Gupta et al 15 in a retrospective study, found that overall stone free rate was 77.5% of patients in miniperc and was 94.0% of patient in standard PCNL respectively. Sarilar et al 9 observed in their study that the success rate of stone clearance was 92.0% in miniperc group and 92.5% in standard PCNL group respectively. Zhu et al 10 in a metaanalysis showed no difference between the miniperc and standard PCNL (P=0.23).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Gupta et al 15 in a retrospective study, found that overall stone free rate was 77.5% of patients in miniperc and was 94.0% of patient in standard PCNL respectively. Sarilar et al 9 observed in their study that the success rate of stone clearance was 92.0% in miniperc group and 92.5% in standard PCNL group respectively. Zhu et al 10 in a metaanalysis showed no difference between the miniperc and standard PCNL (P=0.23).…”
Section: Discussionmentioning
confidence: 89%
“…A retrospective study by Giusti et al 14 found that the mean stone size was 1.67±0.5 in miniperc and 1.83±0.8 for standard PCNL. Sarilar et al 9 showed that size did not correlate significantly with miniperc and standard PCNL (P=0.730).…”
Section: Discussionmentioning
confidence: 96%